2017
DOI: 10.1515/saeb-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of the Financial Behavior of Investors with Brand Approach (Case Study: Tehran Stock Exchange)

Abstract: Behavioral science in the field of finance and investment is among new topics raised in recent years. The relationship between financial sciences and other fields of social sciences such as financial psychology has caused researchers to do many researches regarding the behavior of investors in the financial markets and their reactions to different situations. Based on the theories of financial behavior, shareholders' decision to buy and sell stocks is under the influence of internal and external psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The investor who selects online trading platforms and receive profits more frequently tend to use online trading platform more often (Rahman et al, 2020). Previous studies indicated positive relationship which influences the intention to use mobile applications (Dasgupta et al, 2011;Nouri et al, 2017). Previous studies reveal that investors who trade excessively tends to exhibit gambling disorders to influence their behavioral intention for a particular trading behavior (Dixon et al, 2018).…”
Section: Facilitating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investor who selects online trading platforms and receive profits more frequently tend to use online trading platform more often (Rahman et al, 2020). Previous studies indicated positive relationship which influences the intention to use mobile applications (Dasgupta et al, 2011;Nouri et al, 2017). Previous studies reveal that investors who trade excessively tends to exhibit gambling disorders to influence their behavioral intention for a particular trading behavior (Dixon et al, 2018).…”
Section: Facilitating Conditionsmentioning
confidence: 99%
“…The gradual shift of retail investors from investing using web browsers to mobile application adoption behavior for e-trading is thus identified as research question in this study. Under the UTAUT framework, perceived risk and perceived return were considered as important predictors of investor behavior in financial markets (Chuang and Chang, 2013;Nouri et al, 2017;Yang and Xie, 2011). The integration of UTAUT framework with the goal contagion theory (Aarts et al, 2004) is considered as another research gaps for technology adoption in behavioral finance domain.…”
Section: Introductionmentioning
confidence: 99%
“…A favorable attitude toward a brand or company with perceived remarkable performance can influence investment intentions (Mathur et al, 2022). Positive attitudes toward a company have been shown to have a positive effect on the purchase of its shares compared to other companies with similar financial risks and returns (Nouri et al, 2017;Aspara and Tikkanen, 2010;Aspara, 2013). Intentions are commonly used as predictors of behavior, and the relationship between purchase intention and actual purchase behavior has been validated in various financial product and service domains (Gardner et al, 2020;Silva et al, 2019;Çal and Lambkin, 2017a;Tornikoski and Maalaoui, 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…These studies emphasize the significance of factors such as brand reputation, firm status within the industry, past stock performance, share price, economic sensitivity and anticipated returns to investors in shaping investment decisions. Investors perceive brand reputation as a means to gain crucial insights into a firm's longterm potential and profitability, ultimately impacting the attractiveness of the firm as an investment destination (Aspara, 2013;Nouri et al, 2017). Consequently, a positive reputation of a company can foster investor confidence and positively influence their investment decisions (Nawrocki and Szwajca, 2022;Cole et al, 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Surajit S. et al (2018), the study has been done in Bangladesh and author recommend in literature that many of influencing factors which these factors significantly effective on investment decisions in stock trade in share market. Bagher A. et al (2017), in term of stock trading the investors and shareholders focus on the factors of social, psychological and financial behavior are studied and affect the behavior of investors and traders and taken into significant external factors in trading of stocks. The impact of external factors was measured on risk and return; attitude towards products and investment purpose were calculated with moderating role of brand information.…”
Section: Literature Reviewmentioning
confidence: 99%